ІМОВІРНІСНІ ВЛАСТИВОСТІ ЕЛЕКТРИЧНИХ ХАРАКТЕРИСТИК ЗАРЯДНОГО КОЛА КОНДЕНСАТОРА ІЗ СТОХАСТИЧНИМ АКТИВНИМ ОПОРОМ - Щерба, А.А.; Супруновська, Н.І.; Іващенко, Д.С. (Інститут електродинаміки НАН України, Київ, 2018)
The approach to the determination of the probability properties (probability density function, probability distribution function, mathematical expectation) of the electrical characteristics of the circuits of electric discharge installations whose active resistance can be changed at random is proposed. It is assumed that such a stochastic resistance is characterized by a continuous random variable whose probabilistic properties are known. As an example, probabilistic properties of the voltage on a capacitor in a first-order circuit with a stochastic active resistance having a uniform probability distribution were investigated. References 10, figures 3.